2009
DOI: 10.4103/0256-4947.55318
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of exercise-induced bronchoconstriction in teenage football players in Tunisia

Abstract: BACKGROUND AND OBJECTIVES:Studies on exercise-induced bronchoconstriction (EIB) in team sports are lacking. The aim of this study was to screen for EIB among amateur teenage football players in Tunisia and to compare EIB prevalence between regions.METHODS:One hundred ninety-six male football players (mean age [SD], 13.5 [0.5] yrs), practicing in three different cities of Tunisia (Tunis, Sousse and Sfax), underwent an outdoor free run of 7 minutes. Forced expiratory volume in one second (FEV1) was recorded prio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Ten studies involving 1773 participants (223 cases of EIB) investigated the prevalence of EIB in child and adolescent athletes. Five studies recruited male soccer players, and other five studies included athletes of different modalities. The pooled prevalence of EIB was 15% (95% CI: 9‐21%) (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ten studies involving 1773 participants (223 cases of EIB) investigated the prevalence of EIB in child and adolescent athletes. Five studies recruited male soccer players, and other five studies included athletes of different modalities. The pooled prevalence of EIB was 15% (95% CI: 9‐21%) (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Thirty‐three studies investigated the prevalence of EIB in general population of children and adolescents. Ten studies reported the prevalence of EIB in child and adolescent athletes, and 23 studies in children and adolescents with asthma.…”
Section: Resultsmentioning
confidence: 99%
“…To date, there have been few studies addressing EIB diagnosis in elite soccer players . Nearly all the studies performed in this athletic group have involved cohorts of nonprofessional adolescent players . In professional rugby union – a sport that shares many characteristics with soccer – the prevalence of asthma/EIB following objective screening was recently found to be 32% .…”
Section: Discussionmentioning
confidence: 99%
“…A total of ten studies with 3129 adolescent athletes were included, and their ages ranged from seven to 20 years. Three studies were conducted in the USA [ 15 - 17 ], one in Greece [ 18 ], one in Tunisia [ 19 ], one in Poland [ 20 ], one in Japan [ 21 ], one in Germany [ 22 ], one in Iran [ 23 ], and one in Brazil [ 24 ]. Five studies were cross-sectional studies [ 15 , 16 , 19 , 21 , 23 ], three were cohort studies [ 18 , 22 , 24 ], one was a prospective study [ 20 ], and one was an observational study [ 17 ].…”
Section: Reviewmentioning
confidence: 99%
“…Most studies have demonstrated that athletes in their adolescence suffer from EIB, which requires regular management. Two studies have reported that low-income communities [ 15 ] and humidity levels [ 19 ] are risk factors for EIB.…”
Section: Reviewmentioning
confidence: 99%